2000
DOI: 10.1038/labinvest.3780096
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Markers for Prostatic Cancer Progression

Abstract: SUMMARY:Despite the high incidence of prostate cancer, only limited data are available on genes or chromosomes specifically involved in its initiation and progression. We have applied comparative genomic hybridization to routinely processed, paraffin-embedded, tissues at different times in prostatic tumor progression to screen the tumor genome for gains and losses. Our panel included specimens derived from 56 different patients: 23 patients with primary, prostate-confined carcinomas; 18 patients with regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 56 publications
13
126
1
1
Order By: Relevance
“…Apart from its participation in hepatocellular carcinoma, gains of 1q21-q22 were also shown related to the progression of other human cancers. The presence of 1q21-q22 amplicon in metastatic lesions of lung cancer, 24,25 head and neck squamous cell carcinoma 26 and prostate cancer 27,28 has further put forward a role for this region in tumor dissemination. In an attempt to elucidate for the underlying affected genes, positional mapping from our group has previously refined the 1q21-q22 amplicon in hepatocellular carcinoma to three affected loci, in which the overexpression of JTB, SHC1, CCT3 and COPA was indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its participation in hepatocellular carcinoma, gains of 1q21-q22 were also shown related to the progression of other human cancers. The presence of 1q21-q22 amplicon in metastatic lesions of lung cancer, 24,25 head and neck squamous cell carcinoma 26 and prostate cancer 27,28 has further put forward a role for this region in tumor dissemination. In an attempt to elucidate for the underlying affected genes, positional mapping from our group has previously refined the 1q21-q22 amplicon in hepatocellular carcinoma to three affected loci, in which the overexpression of JTB, SHC1, CCT3 and COPA was indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Gains on 7q have also been signified in the advanced tumor stages of prostate cancer and appeared to be potential genetic discriminators for the prognosis of patients after radical prostatectomy. 27 It has been further suggested that the distal 7q3 regions are likely to harbor genes affecting the progression of prostate cancer from latent to invasive disease. 34 In chronic infections of the liver, elevated levels of hepatocyte growth factor (7q21) are often detected and have been shown to induce upregulation of MET expression in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Based on genomewide scans, such susceptibility loci and genetic alterations were attributed to chromosomes, 1,7,8,10,12,17,18,20, X, and the Y chromosome. [9][10][11][12][13][14] A large amount of data has been generated about alterations, aberrations, rearrangements, gain, or loss of Y-chromosome materials in prostate cancer using different techniques of molecular cytogenetics. [15][16][17][18][19][20] The simple fact that the Y chromosome and prostate cancer have male-specificity in common lead many researchers to investigate if there is Y involvement in such a male-specific cancer, however, yet there is no clear conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The gain of 8q is one of the most common chromosomal alterations in late-stage prostate cancer. By CGH, it is found in about 70% to 90% of hormone-refractory or metastatic prostate carcinomas, and it seems to be associated with poor prognosis (Alers et al, 2000;Cher et al, 1996;Nupponen et al, 1998b). We and others have previously mapped the minimal commonly amplified regions to two separate chromosomal fragments, 8q21 and 8q23-q24 (Cher et al, 1996;Nupponen et al, 1998b).…”
Section: Porkka Et Almentioning
confidence: 99%